The Identification and Utilization of Maslow's Hierarchy of Needs in Ghana's Senior High Mathematics Curriculum - Oppong-Gyebi, Emmanuel; Belbase, Shashidar; Kwadwo Amo-Asante (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
This study identifies all observable action verbs in the Senior High School core mathematics curriculum and links them to Maslow’s Hierarchy of Needs. All the 217 identified action verbs were further grouped in a matrix form in the order of Maslow’s hierarchy of needs against the major headings as stated above in the syllabus. The study collated the frequencies and percentages of the action verbs in a matrix form using Microsoft Office Excel 2019. The study revealed that each of the verbs represents the key profile component of each objective. The study revealed that teachers should evaluate students appropriately in their knowledge and understanding, invention and creativity, analysis, and application, as these represent the growing needs in Maslow’s Hierarchy of Needs. It also revealed how the curriculum designers intended for students to fulfill the majority of their needs in the teaching and learning column of Maslow's hierarchy matrix through these activities. To accomplish the predetermined goal, the study advises teachers to employ these action verbs as they arise in the curriculum's objective for the subject being studied. Future studies should look into whether the mathematics curriculum's application of 21st-century skills aligns with the needs hierarchy's stages.